PERAN SENI TARI DALAM PERKEMBANGAN SOSIAL ANAK USIA DINI: THE ROLE OF DANCE IN EARLY CHILDHOOD SOCIAL DEVELOPMENT - Hanifa, Hasti Maulidia; Syafila, Fitria Nala; Faisal, Vava Imam Agus (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2025)
Kindergarten (TK) children are unique individuals and have unique characteristics, both in terms of cognitive, social, emotional, language, physical and motor skills, and are experiencing a very rapid development process. Dance learning is an aesthetic experience for children that can foster creativity and help children's physical and spiritual development. Dance learning for kindergarten age children can be done through one of the elements in dance itself, one of which is the element of time. In the element of time there are elements of tempo, rhythm, accent and duration which can be used to develop aspects of children's development. In its implementation, it is hoped that children can be given active learning to develop aspects of abilities that are appropriate to the child's development. The role of the teacher as a facilitator and motivator in its implementation is very important. Teachers can apply concepts through demonstration methods and direct practice in an interesting and fun learning atmosphere.